Paňcabuddha Perception of Caryā - Shrestha, Arun (SIRJANĀ – A Journal Of Arts and Art Education, 2018)
My study of ahorātrapadasādhavidhi is the study of caryā repertoire and in this repertoire of caryā of ‘performing ritual’, paňcabuddha is the store house of vajrayāna philosophical system from which emerges the bunch of deities who fill the kaleidoscopic scenario of visualization process in the religious practice of vajrayāna religion. The play of symbolism is swung to the extremes of space and beyond through the projection of akşobhya, vairocana, amitābha, ratnasambhava and amoghasiddhi as five divine forces or paňcabuddha representing paňcaskandha, driving all the sentient beings to their ‘nonexistent existence’. On the basis of the reliance on the ‘visualization’ of paňcabuddha, a path to nirvāna is eased through the ‘realization’ of śunyatā and ultimate liberation of humanity a mass.